Levosimendan: evolution over last two decades - Gupta, Kishore; Shah, Dhiren; Naik, Dhaval (International Journal of Advances in Medicine, 2022)
Levosimendan was maiden agent at the time of its emergence, promoting inotropy mainly through calcium sensitization of cardiac troponin C (cTnC). Levosimendan seems a lucrative option but has not demonstrated a clear superiority to other inotropes in well-designed trials. We searched the PubMed database and reviewed the pertinent studies published till 2021 and summarized various trials/studies to come to a consensus regarding its indications in cardiac patients. Patients with decompensated heart failure requiring inotropic support and receiving beta-blockers represent most widely accepted indication. Levosimendan infusions are increasingly used to facilitate extracorporeal membrane oxygenation (ECMO) weaning and avoiding hospitalizations in patients with end-stage heart failure. Levosimendan doesn’t seem to have long term survival benefit in ventricular dysfunction patients undergoing surgery. The evidence supporting the role in right ventricular failure is not well-established. These lines of evidence require further investigation and their clinical significance needs to be evaluated in specifically designed prospective trials.